Laminate and packaging bag
Patent Information
- Application Number
- JP2023129919
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
Smart Images

Figure 2025025282000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate and a packaging bag. [Background technology]
[0002] Semiconductor products are manufactured or used in clean environments such as clean rooms with high levels of cleanliness, because the quality of the products can be reduced if foreign matter such as dust and dirt adheres to the products. When an item is brought into such an environment, a package in which the item is contained in a bag made of plastic film is often used. Therefore, high cleanliness is also required for packaging bags that contain items that require a high level of cleanliness, such as semiconductor products.
[0003] Conventionally, a package is manufactured as follows using a double bag having at least an inner bag and an outer bag (see, for example, Patent Document 1). First, an item is placed inside the inner bag, which is vacuum degassed, and the opening of the inner bag is sealed. Next, the inner bag is placed inside the outer bag, which is vacuum degassed, and the opening of the outer bag is sealed. The item is packaged in this double packaging, or triple packaging as necessary. When the item is to be used, the outer bag is opened in the antechamber of the clean room, the clean inner bag is opened inside the clean room, and the item is removed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-126437 A Summary of the Invention [Problem to be solved by the invention]
[0005] When packaging an article using double or triple vacuum packaging, the vacuum packaging is performed multiple times. This may result in low work efficiency in packaging the article. Furthermore, when opening the packaging bag, the multiple openings may be troublesome. Furthermore, in recent years, attention has been focused on addressing environmental issues such as marine plastic pollution and global warming. Therefore, packaging materials and the like are required to have high recyclability. Furthermore, it may be desirable for such packaging bags to have gas barrier properties in order to suppress the effects of oxygen or humidity on the article in the bag.
[0006] An object of the present disclosure is to provide a laminate which is suitable as a packaging material capable of packaging articles used in clean environments and which has excellent recyclability and gas barrier properties. [Means for solving the problem]
[0007] The present inventors have investigated the production of a packaging bag using a laminate having a peel-off portion and a main body portion, the production of the laminate mainly from polyolefin, and the provision of a barrier layer on the peel-off portion and / or the main body portion. By peeling off the peel-off portion of the packaging bag in the antechamber of the clean room, the packaging bag in a clean state can be brought into the clean room. Based on this knowledge, the present inventors have found that the above problem can be solved by a laminate having the following configuration.
[0008] A laminate according to one embodiment of the present disclosure comprises at least a peel-off portion and a main body portion, the peel-off portion being provided so as to be peelable from the main body portion, the peel-off portion containing polyolefin as a main component and the polyolefin content in the peel-off portion being 80 mass% or more based on the mass of the peel-off portion, the main body portion containing polyolefin as a main component and the polyolefin content in the main body portion being 80 mass% or more based on the mass of the main body portion, the main body portion comprising at least a heat-fusible resin layer containing polyolefin as a main component, and at least one of the peel-off portion and the main body portion comprising a barrier substrate, the barrier substrate comprising a polyolefin substrate containing polyolefin as a main component and a vapor-deposited film provided on the polyolefin substrate. Effect of the Invention
[0009] According to the present disclosure, it is possible to provide a laminate which is suitable as a packaging material capable of packaging items used in a clean environment and has excellent recyclability and gas barrier properties. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of one embodiment of a laminate of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view of one embodiment of a laminate of the present disclosure. [Diagram 3] FIG. 3 is a schematic cross-sectional view of one embodiment of the packaging bag of the present disclosure. [Figure 4] FIG. 4 is a front view of one embodiment of the packaging bag of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present disclosure will be described in detail. The present disclosure can be implemented in many different forms, and is not to be interpreted as being limited to the description of the embodiments exemplified below. In the drawings, the width, thickness, shape, etc. of each layer may be shown diagrammatically in order to make the explanation clearer, but these are merely examples and do not limit the interpretation of the present disclosure. In this specification and each figure, elements similar to those already explained with respect to the previous figures are given the same reference numerals, and detailed explanations may be omitted as appropriate.
[0012] In the present disclosure, when multiple upper limit candidates and multiple lower limit candidates are listed for a certain parameter, the numerical range of the parameter may be configured by combining any one upper limit candidate and any one lower limit candidate. Examples of the above parameters include physical property values, component content ratios, and layer thicknesses. As an example, the description "Parameter B is preferably A1 or more, more preferably A2 or more, and even more preferably A3 or more. Parameter B is preferably A4 or less, more preferably A5 or less, and even more preferably A6 or less." will be explained. In this example, the numerical range of parameter B may be A1 or more and A4 or less, A1 or more and A5 or less, A1 or more and A6 or less, A2 or more and A4 or less, A2 or more and A5 or less, A2 or more and A6 or less, A3 or more and A4 or less, A3 or more and A5 or less, or A3 or more and A6 or less.
[0013] In the following description of this specification, each of the components (e.g., polyolefins such as polyethylene and polypropylene, α-olefins, resin materials, and additives) may be used alone or in combination of two or more. For example, the polyolefin in the following description may be used alone or in combination of two or more.
[0014] In this specification, polyethylene refers to a polymer in which the content of ethylene-derived structural units in all repeating structural units exceeds 50 mol%. In this polymer, the content of ethylene-derived structural units is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and particularly preferably 95 mol% or more. The content is measured by NMR.
[0015] In this specification, polyethylene may be a homopolymer of ethylene, or a copolymer of ethylene and an ethylenically unsaturated monomer other than ethylene. Examples of the ethylenically unsaturated monomer other than ethylene include α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene, vinyl monomers such as vinyl acetate and vinyl propionate, (meth)acrylic acid, and (meth)acrylic acid esters such as methyl (meth)acrylate and ethyl (meth)acrylate.
[0016] In this specification, examples of polyethylene include high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE) and linear low density polyethylene (LLDPE), as well as ethylene-α-olefin copolymers, ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid copolymers and ethylene-(meth)acrylic acid ester copolymers.
[0017] In this specification, the density of polyethylene is as follows: The density of the high density polyethylene is preferably 0.945 g / cm 3 The density of the high density polyethylene is preferably greater than 0.965 g / cm 3 The density of the medium density polyethylene is preferably 0.932 g / cm 3 Exceeds 0.945g / cm 3The density of the low density polyethylene is preferably 0.860 g / cm 3 More than 0.932g / cm 3 Less than or equal to 0.900 g / cm 3 More than 0.932g / cm 3 The density of the linear low density polyethylene is preferably 0.860 g / cm 3 More than 0.932g / cm 3 Less than or equal to 0.900 g / cm 3 More than 0.932g / cm 3 The density of polyethylene is measured in accordance with JIS K7112:1999, Method D (density gradient tube method, 23°C).
[0018] Low-density polyethylene is, for example, polyethylene obtained by polymerizing ethylene by high-pressure polymerization (high-pressure low-density polyethylene). Linear low-density polyethylene is, for example, polyethylene obtained by polymerizing ethylene and a small amount of α-olefins by a polymerization method using a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst.
[0019] Polyethylenes with different densities or branches can be obtained by appropriately selecting a polymerization method. For example, it is preferable to carry out polymerization in one or more stages by using a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst as a polymerization catalyst, by any of gas phase polymerization, slurry polymerization, solution polymerization, and high pressure ion polymerization.
[0020] In this specification, polyethylene may be polyethylene derived from biomass (hereinafter also referred to as "biomass polyethylene"). That is, as a raw material for obtaining polyethylene, ethylene derived from biomass may be used instead of ethylene obtained from fossil fuels. Since biomass polyethylene is a carbon-neutral material, it is possible to reduce the environmental load caused by the laminate or packaging bag. Biomass polyethylene can be produced, for example, by the method described in JP 2013-177531 A. Commercially available biomass polyethylene may be used.
[0021] In this specification, polyethylene may be mechanically recycled or chemically recycled. This can reduce the environmental impact of laminates or packaging bags. Mechanical recycling is generally a method in which recovered polyethylene films, etc. are crushed, washed with an alkali to remove dirt and foreign matter from the film surface, and then dried at high temperature and reduced pressure for a certain period of time to diffuse contaminants remaining inside the film, thereby decontaminating the film and removing the dirt from the film, and returning it to polyethylene. Chemical recycling is generally a method in which recovered polyethylene films, etc. are decomposed to the monomer level, and the monomers are polymerized again to obtain polyethylene.
[0022] In the present specification, examples of polypropylene include propylene homopolymers, propylene random copolymers such as propylene-α-olefin random copolymers, and propylene block copolymers such as propylene-α-olefin block copolymers. The details of the α-olefins are as described above, and the α-olefin may also include ethylene.
[0023] As the polypropylene, biomass-derived polypropylene may be used. As the polypropylene, mechanically recycled or chemically recycled polypropylene may be used. As for polyolefins other than polyethylene and polypropylene, biomass-derived polyolefins or mechanically recycled or chemically recycled polyolefins may be used.
[0024] In this specification, the melt flow rate (MFR) of polyolefin is preferably 0.1 g / 10 min or more, more preferably 0.2 g / 10 min or more, even more preferably 0.5 g / 10 min or more, and preferably 50 g / 10 min or less, more preferably 30 g / 10 min or less, even more preferably 20 g / 10 min or less, and particularly preferably 10 g / 10 min or less, for example, 0.1 g / 10 min or more and 50 g / 10 min or less, in accordance with JIS K7210-1:2014, measured by method A under a load of 2.16 kg. The measurement temperature of MFR is set according to the melting point of polyolefin, etc. The measurement temperature of MFR is 190 ° C. for polyethylene and 230 ° C. for polypropylene.
[0025] In this specification, the "main component" in a part, layer, substrate, film, etc. refers to a component whose content in the part, layer, substrate, or film is more than 50 mass%, preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more.
[0026] [Laminate] The laminate of the present disclosure includes at least a release portion and a main body portion. The release portion is provided so as to be peelable from the main body portion. In this specification, a film consisting of the release portion obtained by peeling the release portion from the main body portion of the laminate of the present disclosure is also referred to as a "release film." The film consisting of the main body portion after the peeling is also referred to as a "packaging film."
[0027] The main body has a first surface and a second surface opposite to the first surface. The peel-off portion is provided on the first surface of the main body. The peel-off portion is in contact with the main body, specifically, in contact with the first surface of the main body. Therefore, the first surface of the main body is usually the peel-off surface when the peel-off portion is peeled off. When a packaging bag is produced using the laminate of the present disclosure, the second surface of the main body faces the storage space of the packaging bag.
[0028] At least one of the peel-off portion and the main body portion of the laminate of the present disclosure includes a barrier substrate. A packaging bag made using such a laminate has excellent gas barrier properties and can, for example, suppress the effects of oxygen or humidity on an article contained in the bag.
[0029] <Main body> The main body contains polyolefin as a main component. The packaging film made of the main body obtained by separating and removing the peelable portion from such a laminate has excellent recyclability. Examples of polyolefin include polyethylene, polypropylene, and polymethylpentene, and polyethylene and polypropylene are preferred.
[0030] The main body "containing polyolefin as a main component" means that the content of polyolefin in the main body is more than 50% by mass, and the polyolefin may be one type or a mixture of two or more types. For example, if the main body contains polyethylene and polypropylene and the total content of polyethylene and polypropylene is more than 50% by mass, the main body is considered to contain polyolefin as a main component even if the content of polyethylene is 50% by mass or less and the content of polypropylene is 50% by mass or less. The same applies to each layer, substrate, release portion, etc. described later.
[0031] The content of polyolefin in the main body is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on the mass of the main body. A laminate having such a main body is excellent in recyclability. Specifically, a packaging film made of the main body obtained by separating and removing the peeling portion from the laminate is excellent in recyclability.
[0032] The "polyolefin content" in the main body means, for example, the polyethylene content when the main body contains only polyethylene as polyolefin, the polypropylene content when the main body contains only polypropylene as polyolefin, and the sum of the polyethylene and polypropylene contents when the main body contains only polyethylene and polypropylene as polyolefin. The same applies to each layer, substrate, release portion, etc. described later.
[0033] The main body may contain a resin material other than polyolefin, such as (meth)acrylic resin, vinyl resin, cellulose resin, polyamide, polyester, and ionomer resin.
[0034] The body may contain additives, such as crosslinkers, antioxidants, antiblocking agents, lubricants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.
[0035] From the viewpoints of strength, gas barrier properties, and heat sealability, the thickness of the main body is preferably 10 μm or more, more preferably 15 μm or more, even more preferably 20 μm or more, and particularly preferably 30 μm or more. From the viewpoint of processability, the thickness of the main body is preferably 250 μm or less, more preferably 200 μm or less, even more preferably 150 μm or less, and particularly preferably 100 μm or less. The thickness of the main body is, for example, 10 μm or more and 250 μm or less.
[0036] In this specification, the thickness of each part, layer, substrate, or film is measured as follows. A block is prepared by embedding the laminate in an embedding resin, and the block is cut using a commercially available rotary microtome at room temperature (25°C) to prepare a cross section of the laminate. The cross section is obtained by cutting the laminate in the thickness direction perpendicular to the main surface. Finishing is performed with a diamond knife. The thickness of each part, layer, substrate, or film is the arithmetic average value of the thicknesses at five points measured by observing the cross section using a scanning electron microscope (SEM).
[0037] The body portion includes at least a heat-sealable resin layer containing polyolefin as a main component. The heat-sealable resin layer forms a second surface of the body portion. In one embodiment, the heat-sealable resin layer in the body portion is in contact with the release portion.
[0038] In one embodiment, the main body portion includes at least a barrier substrate and a heat-sealable resin layer. A packaging bag made using such a laminate has excellent gas barrier properties, and can suppress the effects of oxygen or humidity on an article contained in the bag, for example. In one embodiment, the main body portion further includes an adhesive layer between the barrier substrate and the heat-sealable resin layer. In one embodiment, the barrier substrate in the main body portion is in contact with the peel-off portion.
[0039] (thermal adhesive resin layer) The heat-sealable resin layer contains polyolefin as a main component. The heat-sealable resin layer functions as a seal layer in a packaging bag including the laminate. When a packaging bag is produced using the laminate of the present disclosure, the heat-sealable resin layer is a layer facing the storage space of the packaging bag.
[0040] Examples of the polyolefin in the heat-sealable resin layer include polyethylene, polypropylene, and polymethylpentene, with polyethylene and polypropylene being preferred, polyethylene being more preferred, and from the viewpoint of heat sealability, linear low-density polyethylene and low-density polyethylene being even more preferred, with linear low-density polyethylene being particularly preferred. Examples of the linear low-density polyethylene include C4-LLDPE, C6-LLDPE, and C8-LLDPE.
[0041] From the viewpoint of heat sealability, the melting point (Tm) of the polyethylene in the heat-fusible resin layer is preferably 140° C. or less, more preferably 130° C. or less, even more preferably 125° C. or less, and is preferably 80° C. or more, more preferably 85° C. or more, even more preferably 90° C. or more, for example, 80° C. or more and 140° C. or less. In this specification, the Tm of the polyethylene is the melting peak temperature obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121:2012.
[0042] The content of polyolefin in the heat-sealable resin layer is preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more. A laminate having such a heat-sealable resin layer has excellent recyclability.
[0043] The thermally adhesive resin layer may contain the above-mentioned resin material. The heat-fusible resin layer may contain the above-mentioned additives.
[0044] The thermally adhesive resin layer may have a single-layer structure or a multi-layer structure. From the viewpoint of heat sealability, the thickness of the heat-fusible resin layer is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and is preferably 150 μm or less, more preferably 100 μm or less, even more preferably 80 μm or less, for example, 5 μm or more and 150 μm or less.
[0045] From the viewpoint of heat sealability, the heat-fusible resin layer is preferably an unstretched layer, more preferably an unstretched film. The unstretched layer (film) is a layer (film) that has not been stretched, for example, an extrusion-molded film that has not been stretched. The concept of "unstretched film" includes not only a film that has not been stretched at all, but also a film that has been slightly stretched due to tension applied during film formation by an inflation method or the like.
[0046] The sealant film corresponding to the heat-sealable resin layer can be produced, for example, by forming a polyolefin or a resin composition thereof into a film by a T-die method, an inflation method, etc. The sealant film may be a coextrusion multilayer film, and can be produced, for example, by a coextrusion film forming method.
[0047] In one embodiment, the sealant film may be surface-treated. Surface treatment methods include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, glow discharge treatment, and chemical treatments such as oxidation treatment using chemicals. This can improve the adhesion between the sealant film and other layers, for example.
[0048] (Barrier substrate) In one embodiment, the barrier substrate comprises a polyolefin substrate containing a polyolefin as a main component, and a vapor-deposited film provided on the polyolefin substrate.
[0049] ((Polyolefin base material)) The polyolefin substrate contains polyolefin as a main component. Examples of the polyolefin in the polyolefin substrate include polyethylene, polypropylene, and polymethylpentene, with polyethylene and polypropylene being preferred, and polypropylene being more preferred. Examples of the polyolefin substrate include a polyethylene substrate containing polyethylene as the main component, a polypropylene substrate containing polypropylene as the main component, and a polymethylpentene substrate containing polymethylpentene as the main component, with the polyethylene substrate and polypropylene substrate being preferred, and the polypropylene substrate being more preferred.
[0050] As the polyethylene constituting the polyethylene substrate, high density polyethylene and medium density polyethylene are preferred from the viewpoints of strength and heat resistance. The polypropylene constituting the polypropylene substrate may be any of a propylene homopolymer, a propylene random copolymer and a propylene block copolymer.
[0051] The content of polyolefin in the polyolefin substrate is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. A laminate including such a polyolefin substrate has excellent recyclability.
[0052] The polyolefin substrate may contain the above-mentioned resin material. The polyolefin substrate may contain the additives described above.
[0053] In one embodiment, the polyolefin substrate is a substrate that has been subjected to a stretching process, i.e., a stretched substrate. The stretched substrate is, for example, excellent in strength, puncture resistance, heat resistance, and transparency. The polyolefin substrate is, for example, a stretched polyethylene substrate, a stretched polypropylene substrate, or a stretched polymethylpentene substrate.
[0054] The stretching process may be uniaxial stretching or biaxial stretching. That is, the stretched substrate may be uniaxially stretched or biaxially stretched. When stretching in the machine direction (flow direction of the substrate, MD direction), the stretching ratio is preferably 2 times or more, more preferably 3 times or more, and preferably 15 times or less, more preferably 13 times or less. When stretching in the width direction (direction perpendicular to the MD direction, TD direction), the stretching ratio is preferably 2 times or more, more preferably 3 times or more, and preferably 15 times or less, more preferably 13 times or less. By setting the stretching ratio at 2 times or more, for example, the strength, heat resistance, and transparency of the substrate can be improved, and the printability of the substrate can be improved. From the viewpoint of the breaking limit of the substrate, the stretching ratio is preferably 15 times or less.
[0055] The polyolefin substrate can be produced, for example, by forming a film from a polyolefin or a resin composition thereof by a T-die method, an inflation method, or the like, and then stretching the film as necessary. The polyolefin substrate may be a coextruded multilayer film, and can be produced, for example, by a coextrusion film formation method.
[0056] In one embodiment, the polyolefin substrate may be subjected to the above-mentioned surface treatment. This can improve, for example, the adhesion between the polyolefin substrate and other layers. An easy-adhesion layer may be provided on the surface of the polyolefin substrate.
[0057] The haze value of the polyolefin substrate is preferably 25% or less, more preferably 15% or less, and even more preferably 10% or less. The smaller the haze value, the more preferable it is, but for example, the lower limit may be 0.1% or 1%. The haze value of the polyolefin substrate is measured in accordance with JIS K7136:2000.
[0058] The polyolefin substrate may have a single layer structure or a multilayer structure. The thickness of the polyolefin substrate is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 30 μm or less, for example, 5 μm or more and 100 μm or less. A laminate having a polyolefin substrate with a thickness of the lower limit or more is, for example, excellent in strength and heat resistance. A laminate having a polyolefin substrate with a thickness of the upper limit or less is, for example, excellent in processability.
[0059] ((evaporated film)) The vapor deposition film is composed of, for example, a metal and / or an inorganic oxide. The vapor deposition film may be a metal vapor deposition film composed of one or more metals, or an inorganic oxide vapor deposition film composed of one or more inorganic oxides. The inorganic oxide vapor deposition film may be a transparent vapor deposition film. When the vapor deposition film is a transparent vapor deposition film, a packaging bag with excellent visibility of the contents can be produced. Examples of metals include aluminum, chromium, tin, nickel, copper, silver, gold, and platinum. Examples of inorganic oxides include aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, barium oxide, and silicon carbide oxide (carbon-containing silicon oxide). Among these, aluminum vapor deposition film, aluminum oxide (alumina) vapor deposition film, silicon oxide (silica) vapor deposition film, or silicon carbide vapor deposition film are preferred.
[0060] The thickness of the vapor-deposited film is preferably 1 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more, from the viewpoint of gas barrier properties. The thickness of the vapor-deposited film is preferably 150 nm or less, more preferably 100 nm or less, and even more preferably 80 nm or less, from the viewpoint of suppressing crack generation in the vapor-deposited film and recyclability of the packaging bag. The thickness of the vapor-deposited film is, for example, 1 nm or more and 150 nm or less.
[0061] The surface of the deposited film may be subjected to the above-mentioned surface treatment. Such a deposited film has, for example, excellent adhesion to adjacent layers.
[0062] Examples of methods for forming the vapor-deposited film include physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition. The vapor-deposited film may be a composite film containing two or more layers of different vapor-deposited films formed by combining both physical vapor deposition and chemical vapor deposition.
[0063] The vacuum level in the deposition chamber was 10 before oxygen was introduced. -2 ~10 -8 After oxygen is introduced, the pressure is preferably about 10 -1 ~10 -6 The pressure is preferably about mbar. The amount of oxygen introduced varies depending on the size of the deposition machine. For the oxygen introduced, an inert gas such as argon gas, helium gas, or nitrogen gas may be used as a carrier gas to the extent that no problems occur. The conveying speed of the polyolefin substrate on which the deposition film is formed is, for example, 10 m / min or more and 800 m / min or less.
[0064] The vapor-deposited film may be a single layer formed by one vapor deposition process, or may be a multilayer formed by multiple vapor deposition processes. When the vapor-deposited film is a multilayer film, each layer may be composed of the same component or different components. Each layer may be formed by the same method or different methods.
[0065] ((Barrier Coat Layer)) The barrier substrate may further include a barrier coat layer on the vapor-deposited film. That is, the barrier substrate may include a polyolefin substrate, a vapor-deposited film, and a barrier coat layer in this order. Such a barrier substrate has, for example, excellent oxygen barrier properties and water vapor barrier properties, and can effectively suppress the occurrence of cracks in the vapor-deposited film when the vapor-deposited film is made of an inorganic oxide such as aluminum oxide or silicon oxide.
[0066] In one embodiment, the barrier coat layer contains a gas barrier resin, such as an ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyamide, polyvinylidene chloride, polyester, polyether polyol, polyester polyol, polyurethane, polyacrylonitrile, or (meth)acrylic resin.
[0067] The content of the gas barrier resin in the barrier coat layer is preferably more than 50% by mass, more preferably 60% by mass or more, and even more preferably 70% by mass or more. Such a barrier coat layer has, for example, excellent gas barrier properties.
[0068] The barrier coat layer may contain the above-mentioned additives.
[0069] The thickness of the barrier coat layer containing the gas barrier resin is preferably 0.01 μm or more, more preferably 0.1 μm or more, from the viewpoint of gas barrier properties. The thickness of the barrier coat layer containing the gas barrier resin is preferably 10 μm or less, more preferably 5 μm or less, from the viewpoint of processability of the laminate and recyclability of the packaging bag. The thickness is, for example, 0.01 μm or more and 10 μm or less.
[0070] The barrier coat layer can be formed, for example, by applying a coating liquid obtained by dissolving or dispersing a material such as a gas barrier resin in water or an appropriate organic solvent onto the vapor-deposited film, and drying the resulting coating liquid.
[0071] In another embodiment, the barrier coat layer is a gas barrier coating film formed by mixing a metal alkoxide, a water-soluble polymer, and optionally a silane coupling agent, and adding water, an organic solvent, and a sol-gel catalyst as required to obtain a gas barrier composition, coating the gas barrier composition on a deposition film, and drying the gas barrier composition. The gas barrier coating film contains a hydrolysis polycondensate obtained by hydrolyzing and polycondensing the above-mentioned metal alkoxide by the sol-gel method. By providing such a barrier coat layer on a deposition film, when the deposition film is made of an inorganic oxide, the gas barrier property can be improved and the occurrence of cracks in the deposition film can be effectively suppressed.
[0072] Examples of metal alkoxides include alkoxysilanes, specifically tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane.
[0073] Examples of the water-soluble polymer include hydroxyl group-containing polymers such as polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Either polyvinyl alcohol or ethylene-vinyl alcohol copolymer may be used, or both may be used in combination, depending on the desired physical properties such as oxygen barrier property, water vapor barrier property, water resistance, and weather resistance. Also, a gas barrier coating film obtained using polyvinyl alcohol and a gas barrier coating film obtained using ethylene-vinyl alcohol copolymer may be laminated. The amount of the water-soluble polymer used is preferably 5 parts by mass or more and 500 parts by mass or less, based on 100 parts by mass of the metal alkoxide.
[0074] As the silane coupling agent, known organic reactive group-containing organoalkoxysilane can be used, and organoalkoxysilane having epoxy group is preferable, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldiethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be mentioned. The amount of the silane coupling agent used is preferably 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the metal alkoxide.
[0075] The gas barrier composition may contain water in a ratio of preferably 0.1 mol or more, more preferably 0.5 mol or more, and preferably 100 mol or less, more preferably 60 mol or less, per mol of metal alkoxide. By making the water content equal to or greater than the lower limit, for example, the oxygen barrier property and water vapor barrier property of the barrier substrate can be improved. By making the water content equal to or less than the upper limit, for example, the hydrolysis reaction can be carried out quickly.
[0076] The gas barrier composition may contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butyl alcohol.
[0077] The sol-gel catalyst is preferably an acid or an amine compound.
[0078] Examples of methods for applying the gas barrier composition include application means such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brush coating, bar coating, and applicator coating.
[0079] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. A gas barrier composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and, if necessary, a silane coupling agent. A polycondensation reaction gradually proceeds in the composition. The composition is applied to the deposition film by a conventional method and dried. This drying causes further polycondensation of the metal alkoxide and the water-soluble polymer (and the silane coupling agent if the composition contains a silane coupling agent) to form a composite polymer layer. The above operation may be repeated to laminate multiple composite polymer layers. For example, the applied composition is heated at a temperature of preferably 20°C or higher, more preferably 50°C or higher, and even more preferably 70°C or higher, and preferably 150°C or lower, more preferably 120°C or lower, and even more preferably 100°C or lower, for 1 second to 10 minutes. This allows the formation of a gas barrier coating film.
[0080] The thickness of the gas barrier coating film is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and is preferably 5 μm or less, more preferably 2 μm or less, even more preferably 1 μm or less, for example, 0.01 μm or more and 5 μm or less. A barrier substrate provided with such a gas barrier coating film has, for example, excellent gas barrier properties, can suppress the occurrence of cracks in a vapor deposition film composed of an inorganic oxide, and also has excellent recyclability and processability of a packaging bag.
[0081] (adhesive layer) In one embodiment, the adhesive layer in the main body is an adhesive layer formed from an adhesive. In one embodiment, the adhesive layer functions as an adhesive layer between the barrier substrate and the heat-fusible resin layer. The adhesive may be any of a one-component curing adhesive, a two-component curing adhesive, and a non-curing adhesive. The adhesive may be a solvent-free adhesive or a solvent-based adhesive, but when the polyolefin substrate constituting the barrier substrate is a polypropylene substrate, a solvent-free adhesive is preferred from the viewpoint of suppressing deterioration of the polypropylene substrate due to a solvent.
[0082] Examples of solvent-free adhesives, i.e., non-solvent laminate adhesives, include polyether adhesives, polyester adhesives, silicone adhesives, epoxy adhesives, and urethane adhesives. Examples of solvent-based adhesives include rubber adhesives, vinyl adhesives, olefin adhesives, silicone adhesives, epoxy adhesives, phenol adhesives, and urethane adhesives. Among these, urethane adhesives are preferred, two-liquid curing urethane adhesives are more preferred, and two-liquid curing urethane adhesives containing polyester polyol and isocyanate compound are even more preferred.
[0083] In one embodiment, the solvent-free adhesive is a two-liquid curing adhesive having a base agent and a curing agent. From the viewpoint of coating suitability, the weight average molecular weight (Mw) of the polymer component contained in the base agent is preferably 800 or more, more preferably 1,200 or more, and preferably 10,000 or less, more preferably 4,000 or less, for example, 800 or more and 10,000 or less. The polydispersity (Mw / Mn) of the polymer component contained in the base agent is preferably 1.2 or more, more preferably 1.5 or more, even more preferably 2.0 or more, preferably 2.8 or less, more preferably 2.7 or less, even more preferably 2.6 or less, particularly preferably 2.5 or less, for example, 1.2 or more and 2.8 or less. Here, Mn is the number average molecular weight of the polymer component contained in the base agent. Each average molecular weight is measured by gel permeation chromatography (GPC) in accordance with JIS K7252-1:2008 and is a value converted into polystyrene.
[0084] In one embodiment, the use of a solventless adhesive allows, for example, a thinner adhesive layer than when a solvent-based adhesive is used, which allows the polyolefin content in the entire laminate to be further increased.
[0085] A solvent-free, two-liquid curing urethane adhesive will be described below. As the urethane adhesive, for example, an adhesive having a base agent containing a polyol compound such as polyester polyol and a curing agent containing an isocyanate compound is preferable.
[0086] Examples of the polyol compound include polyester polyol, polyether polyol, polycarbonate polyol, and (meth)acrylic polyol. Among these, polyester polyol is preferred. The polyester polyol has, for example, a polyester structure or a polyester polyurethane structure as a main skeleton.
[0087] From the viewpoint of coating suitability, the weight average molecular weight (Mw) of the polyol compound such as polyester polyol is preferably 800 or more, more preferably 1,200 or more, and preferably 10,000 or less, more preferably 4,000 or less, for example, 800 or more and 10,000 or less. The polydispersity (Mw / Mn) of the polyol compound such as polyester polyol is preferably 1.2 or more, more preferably 1.5 or more, even more preferably 2.0 or more, preferably 2.8 or less, more preferably 2.7 or less, even more preferably 2.6 or less, particularly preferably 2.5 or less, for example, 1.2 or more and 2.8 or less. Here, Mn is the number average molecular weight of the polyol compound. Each average molecular weight is measured by gel permeation chromatography (GPC) in accordance with JIS K7252-1:2008 and is a value converted into polystyrene.
[0088] The isocyanate compound has two or more isocyanate groups in one molecule. Examples of the isocyanate compound include aromatic isocyanates and aliphatic isocyanates. The isocyanate compound may be a blocked isocyanate compound obtained by addition reaction using a known isocyanate blocking agent by a known and conventional appropriate method.
[0089] The thickness of the adhesive layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.5 μm or more. The thickness of the adhesive layer is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 6 μm or less, even more preferably 4 μm or less, and particularly preferably 3 μm or less. The thickness of the adhesive layer is, for example, 0.1 μm or more and 10 μm or less.
[0090] In one embodiment, the adhesive layer in the main body is an extruded resin layer containing polyolefin as a main component. Details of the extruded resin layer will be described later. When the barrier substrate is disposed so that the vapor-deposited film in the barrier substrate faces the heat-fusible resin layer, the adhesive layer is preferably an adhesive layer formed from an adhesive, from the viewpoint of suppressing thermal deterioration of the vapor-deposited film.
[0091] <Peeling part> The release portion contains polyolefin as a main component. The release film obtained by separating and removing the release portion from such a laminate has excellent recyclability. Examples of polyolefin include polyethylene, polypropylene, and polymethylpentene, and polyethylene and polypropylene are preferred.
[0092] The content of polyolefin in the release part is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on the mass of the release part. A laminate having such a release part has excellent recyclability. Specifically, a release film obtained by peeling the release part from the above-mentioned laminate has excellent recyclability.
[0093] The release portion may contain the above-mentioned resin material. The release portion may contain the above-mentioned additives.
[0094] From the viewpoint of releasability, strength and heat resistance, the thickness of the peeling portion is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, and particularly preferably 30 μm or more. From the viewpoint of processability, the thickness of the peeling portion is preferably 250 μm or less, more preferably 200 μm or less, even more preferably 150 μm or less, and particularly preferably 100 μm or less. The thickness of the peeling portion is, for example, 5 μm or more and 250 μm or less.
[0095] The polyolefin contained as a main component in the layer in contact with the main body in the peeling portion is preferably different in type from the polyolefin contained as a main component in the layer in contact with the peeling portion in the main body. A laminate having such a configuration has moderate adhesion and small peel strength between the peeling portion and the main body. Therefore, the peeling portion can be suppressed from floating from the main body during the production and storage of the laminate, and the peeling portion can be easily peeled from the main body. The "different types" of polyolefins refer to polyolefins that are classified differently at such levels, such as polyethylene, polypropylene, and polymethylpentene. Examples of polyolefins that are different in type include a case where one polyolefin is polyethylene and the other polyolefin is polypropylene. Since the compatibility between different types of polyolefins is usually not high, the adhesive strength between the layers tends to be low.
[0096] In one embodiment, the release portion includes at least a surface resin layer containing polyolefin as a main component. In one embodiment, the release portion includes at least the surface resin layer and an adhesive layer in contact with the main body portion.
[0097] (Surface resin layer) The surface resin layer contains polyolefin as a main component. Examples of polyolefins in the surface resin layer include polyethylene, polypropylene and polymethylpentene, with polyethylene and polypropylene being preferred, polyethylene being more preferred, linear low-density polyethylene being even more preferred from the viewpoint of further improving the extensibility and puncture resistance of the laminate, and high-density polyethylene being even more preferred from the viewpoint of further improving the heat resistance of the laminate and packaging bag.
[0098] From the viewpoint of heat resistance, the melting point (Tm) of the polyethylene in the surface resin layer is preferably 100°C or higher, more preferably 105°C or higher, even more preferably 110°C or higher, particularly preferably 120°C or higher, and preferably 140°C or lower.
[0099] The content of polyolefin in the surface resin layer is preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more. A laminate having such a surface resin layer has excellent recyclability.
[0100] The surface resin layer may contain the above-mentioned resin material. The surface resin layer may contain the above-mentioned additives.
[0101] From the viewpoints of the strength, heat resistance, processability and recyclability of the laminate, the thickness of the surface resin layer is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and is preferably 150 μm or less, more preferably 100 μm or less, even more preferably 80 μm or less, for example, 5 μm or more and 150 μm or less.
[0102] The resin film corresponding to the surface resin layer can be produced, for example, by forming a film from polyolefin or a resin composition thereof by a T-die method, an inflation method or the like.
[0103] In one embodiment, the resin film may be subjected to the above-mentioned surface treatment. This can improve the adhesion between the resin film and other layers, for example. An easy-adhesion layer may be provided on the surface of the resin film.
[0104] (adhesive layer) In one embodiment, the adhesive layer in the peeling portion is an extruded resin layer containing polyolefin as a main component. Examples of the polyolefin in the extruded resin layer include polyethylene, polypropylene, and polymethylpentene, and polyethylene and polypropylene are preferred, with polyethylene being more preferred. From the viewpoint of adhesiveness, low-density polyethylene and linear low-density polyethylene are preferred as the polyethylene in the extruded resin layer.
[0105] In one embodiment, the extruded resin layer in the peeling portion is in contact with the polyolefin substrate constituting the barrier substrate in the main body portion. The polyolefin in the extruded resin layer is preferably of a different type from the polyolefin in the polyolefin substrate constituting the barrier substrate. A laminate having such a configuration has appropriate adhesion and small peel strength between the extruded resin layer and the barrier substrate. Therefore, during the production and storage of the laminate, it is possible to suppress lifting of the peeling portion from the main body portion, and the peeling portion can be easily peeled from the main body portion.
[0106] From the viewpoints of film-forming ability and processability, the MFR of the polyethylene in the extruded resin layer is preferably 1 g / 10 min or more, more preferably 3 g / 10 min or more, even more preferably 5 g / 10 min or more, and is preferably 30 g / 10 min or less, more preferably 25 g / 10 min or less, even more preferably 20 g / 10 min or less, for example, 1 g / 10 min or more and 30 g / 10 min or less.
[0107] From the viewpoint of a balance between heat resistance and adhesion, the melting point (Tm) of the polyethylene in the extruded resin layer is preferably 100°C or higher, and preferably 140°C or lower, more preferably 130°C or lower, and even more preferably 125°C or lower, for example, 100°C or higher and 140°C or lower.
[0108] The content of polyethylene in the extruded resin layer is preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass. A laminate including such an extruded resin layer has excellent recyclability.
[0109] The extruded resin layer may contain the above-mentioned additives.
[0110] The thickness of the extruded resin layer is preferably 5 μm or more, more preferably 10 μm or more, and is preferably 40 μm or less, more preferably 30 μm or less, for example, 5 μm or more and 40 μm or less. A laminate including such an extruded resin layer has, for example, excellent interlayer adhesion and recyclability.
[0111] The extruded resin layer can be formed, for example, by melting a polyolefin or a resin composition thereof and extruding it onto a resin film or a barrier substrate. The melting temperature at this time is preferably 280° C. or higher, more preferably 290° C. or higher, and preferably 340° C. or lower, more preferably 335° C. or lower, for example, 280° C. or higher and 340° C. or lower.
[0112] In one embodiment, the extruded resin layer functions as an adhesive layer between the resin film corresponding to the surface resin layer and the barrier substrate included in the main body portion. A laminate including such an extruded resin layer can have a high polyolefin content and is excellent in recyclability, and has an appropriate peel strength between the peeled portion and the main body portion, resulting in excellent peelability of the peeled portion.
[0113] In one embodiment, it is preferable that the extruded resin layer contains polyethylene as a main component, the polyolefin substrate constituting the barrier substrate is a polypropylene substrate, and the extruded resin layer is in contact with the polypropylene substrate. A laminate having such a configuration has moderate adhesion and small peel strength between the extruded resin layer and the barrier substrate. Therefore, during the production and storage of the laminate, it is possible to suppress lifting of the peeled portion from the main body portion, and the peeled portion can be easily peeled from the main body portion. From this viewpoint, it is preferable not to provide an easy-adhesion layer between the extruded resin layer and the barrier substrate. The thickness of the easy-adhesion layer is generally 0.05 μm or more and 3 μm or less.
[0114] <Print layer> The laminate of the present disclosure may have a printed layer on the surface of the barrier substrate and the resin film. Examples of images contained in the printed layer include characters, patterns, symbols, and combinations thereof. The printed layer may be formed using, for example, an ink derived from biomass. This can, for example, further reduce the environmental load.
[0115] Examples of methods for forming the printed layer include conventionally known printing methods such as gravure printing, offset printing, and flexographic printing. Among these, flexographic printing is preferred from the viewpoint of reducing the environmental load.
[0116] <Peel strength> The peel strength between the peeling portion and the main body is preferably 1.0 N / 15 mm width or less, more preferably 0.9 N / 15 mm width or less, even more preferably 0.8 N / 15 mm width or less, even more preferably 0.7 N / 15 mm width or less, and particularly preferably 0.6 N / 15 mm width or less. In the case of a laminate having such a peel strength, the peeling portion can be easily peeled from the main body with a moderate force without damaging the main body. The above peel strength is, for example, 0.01 N / 15 mm width, 0.05 N / 15 mm width, or 0.1 N / 15 mm width or more, preferably 0.15 N / 15 mm width or more. In the case of a laminate having such a peel strength, the lifting of the peeling portion from the main body can be suppressed, the appearance of the laminate is excellent, and the peeling portion can be suppressed from being peeled off from the main body at an unintended time. In addition, even if heat-sealed, the increase in the peel strength at the sealed portion can be suppressed to a range that can be peeled off by hand.
[0117] The peel strength is measured under the conditions of a peel angle of 180 degrees and a test speed of 50 mm / min. Specifically, the laminate is cut to cut out a test piece having a width of 15 mm and a length of 100 mm. The peeled portion at one end of the length direction of the test piece is peeled and folded back, and the end of the partially peeled peeled portion (peeling film) is attached to one grip of a tensile tester, and the end of the main body (packaging film) after the partial peeling is attached to the other grip of the tensile tester. The initial chuck distance is 100 mm. Next, the grip to which the end of the peeled portion is attached is pulled at a speed of 50 mm / min in a direction of 180 degrees with respect to the surface of the test piece while maintaining the position of the test piece so that the angle is maintained, and the maximum strength (N) is measured. The maximum strength (N) measured for the 15 mm wide test piece is taken as the peel strength (N / 15 mm width).
[0118] <Configuration and manufacturing method of laminate> 1 and 2 show schematic cross-sectional views of one embodiment of the laminate of the present disclosure. The laminate 1 in FIG. 1 includes a peel-off portion 2 and a main body portion 4 in this order. The laminate 1 in Fig. 2 comprises, in this order, a surface resin layer 30, an extruded resin layer 36A, a barrier substrate 10, an adhesive layer 36B, and a heat-sealable resin layer 20. In the laminate 1 in Fig. 2, the barrier substrate 10 comprises a polyolefin substrate 12 and a vapor-deposited film 14. The peel-off portion 2 comprises the surface resin layer 30 and the extruded resin layer 36A. The main body portion 4 comprises the barrier substrate 10, the adhesive layer 36B, and the heat-sealable resin layer 20.
[0119] The total thickness of the laminate of the present disclosure is preferably 15 μm or more, more preferably 30 μm or more, even more preferably 50 μm or more, even more preferably 70 μm or more, and particularly preferably 90 μm or more, from the viewpoint of the strength and heat resistance of the laminate.The total thickness of the laminate of the present disclosure is preferably 350 μm or less, more preferably 300 μm or less, even more preferably 250 μm or less, even more preferably 200 μm or less, and particularly preferably 150 μm or less, from the viewpoint of the processability of the laminate.The total thickness of the laminate of the present disclosure is, for example, 15 μm or more and 350 μm or less.
[0120] The polyolefin content in the laminate of the present disclosure is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on the mass of the laminate. Such a laminate has excellent recyclability.
[0121] The oxygen permeability (unit: cc / (m 2 The oxygen permeability is preferably 3.0 or less, more preferably 2.0 or less, further preferably 1.0 or less, and particularly preferably 0.5 or less. The lower limit of the oxygen permeability may be, for example, 0.01. The oxygen permeability is measured in accordance with JIS K7126-2:2006 at a temperature of 23°C and a humidity of 90% RH.
[0122] The water vapor permeability (unit: g / (m 2·day)) is preferably 10 or less, more preferably 8.0 or less, even more preferably 6.0 or less, even more preferably 4.0 or less, and particularly preferably 2.0 or less. The lower limit of the water vapor permeability may be, for example, 0.01 or 0.05. The water vapor permeability is measured in accordance with JIS K7129-2:2019 at a temperature of 40°C and a humidity of 90% RH.
[0123] The laminate of the present disclosure can be produced, for example, by bonding a resin film, a barrier substrate, and a sealant film together via an adhesive layer. The resin film corresponds to the above-mentioned surface resin layer. The sealant film corresponds to the above-mentioned heat-sealable resin layer. Details of the adhesive layer are as described above. Specifically, the laminate can be produced by laminating the resin film, the barrier substrate, and the sealant film using a melt extrusion lamination method, a dry lamination method using a solvent-based adhesive, or a non-solvent lamination method using a solvent-free adhesive (these methods may be combined). Alternatively, the heat-sealable resin layer may be formed by extruding a polyolefin or a resin composition thereof using a T-die extruder after performing a well-known easy-adhesion treatment such as the above-mentioned surface treatment or formation of an easy-adhesion layer on one side of the barrier substrate.
[0124] In one embodiment, a barrier substrate and a sealant film are bonded together by a dry lamination method using a solvent-based adhesive, or a non-solvent lamination method using a solvent-free adhesive, and the barrier substrate and a resin film after this bonding are then bonded together by a melt extrusion lamination method, thereby producing a laminate. In one embodiment, the resin film and the barrier substrate are laminated together by melt extrusion lamination, and the barrier substrate and the sealant film after this lamination are then laminated together by dry lamination using a solvent-based adhesive, or by non-solvent lamination using a solvent-free adhesive, to produce a laminate. By not providing an easy-adhesion layer between the barrier substrate and the extruded resin layer, the peel strength between the barrier substrate and the extruded resin layer can be kept low, thereby producing a laminate in which the peel portion can be easily peeled from the main body portion.
[0125] By carrying out the above manufacturing in a clean environment, it is possible to prevent foreign matter such as dust and dirt from adhering to the first surface of the main body from the time of manufacturing the laminate to the time of peeling and removing the peelable portion. When using the packaging bag, the first surface of the main body is exposed by peeling and removing the peelable portion from the main body of the laminate. This first surface is a clean surface in which the adhesion of foreign matter is prevented.
[0126] [Application] The laminate of the present disclosure can be suitably used as a packaging material for forming a packaging bag. The second surface of the main body of the laminate forms an inner surface (a surface that comes into contact with an article in the packaging bag) facing the storage space in the packaging bag.
[0127] A high level of cleanliness is required for an article used in a clean environment such as a clean room. A packaging bag containing the article is brought into the clean environment and opened. Therefore, a high level of cleanliness is also required for the packaging bag. That is, when the packaging bag containing the article is brought into the clean environment, it is necessary to prevent foreign matter such as dust and dirt from adhering to the surface of the packaging bag and the foreign matter from entering the clean environment together with the packaging bag. By using a packaging bag including the laminate of the present disclosure, the intrusion of such foreign matter can be prevented, for example, as follows.
[0128] First, an article is placed in the packaging bag of the present disclosure, and degassed by vacuum degassing or the like as necessary, and the opening of the packaging bag is sealed to obtain a package in which the article is placed in the packaging bag. Degassing is not limited to vacuum degassing as long as the gas in the packaging bag can be removed. For example, degassing may be performed by pressing the packaging bag from the outside using a pressing member. The packaging body is brought into an anterior chamber of a clean environment. Here, the peelable portion (peeling film) of the laminate constituting the packaging bag is peeled and removed. This exposes the first surface of the main body portion (packaging film) of the laminate constituting the packaging bag. As described above, the first surface of the main body portion is a clean surface in which adhesion of foreign matter is suppressed. The packaging bag obtained by peeling and removing the peelable portion has a small amount of foreign matter attached to its surface. Such a packaging bag is brought into a clean environment. In the clean environment, the packaging bag is opened to take out the article and use it. In this way, intrusion of foreign matter into the clean environment together with the packaging bag is suppressed.
[0129] According to the above configuration, the packaging bag of the present disclosure does not need to be configured as a double-ply bag having at least an inner bag and an outer bag, or a triple-ply or more bag. However, there is no restriction on using the packaging bag of the present disclosure as an outer bag in a double-ply bag or a triple-ply or more bag.
[0130] Examples of the goods to be stored in the packaging bag include semiconductor products such as ICs and LSIs, semiconductor-related parts such as valves for semiconductor devices and filters for semiconductor manufacturing, precision machinery, magnetic disks, silicon wafers, O-rings, bellows, pharmaceutical products, products for regenerative medicine, and medicinal liquid products such as diluents for blood cell testing devices and artificial dialysis fluids. Examples of the goods to be stored in the packaging bag include dustproof clothing, dustproof gloves, and tools used in clean environments.
[0131] The packaging bag of the present disclosure includes the laminate of the present disclosure. The packaging bag of the present disclosure has, for example, a storage section for storing contents and a seal section where the heat-sealable resin layers of the laminate are joined together. The seal section includes an inner edge that defines the storage section.
[0132] In one embodiment, the packaging bag of the present disclosure includes a top sheet constituting the front surface and a back sheet constituting the back surface. The top sheet may be composed of one laminate of the present disclosure, and the back sheet may be composed of another laminate of the present disclosure. The top sheet and the back sheet may be integrated, or may be composed of one laminate of the present disclosure.
[0133] The packaging bag usually has a heat-sealed portion (sealed portion). Examples of the heat-sealing method include bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, and ultrasonic sealing.
[0134] Examples of packaging bags include packaging bags of various shapes such as a standing pouch type, a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grooving seal type (pillow seal type), a pleated seal type, a flat bottom seal type, a square bottom seal type, and a gusset type. The planar shape of the packaging bag may be, for example, rectangular or a shape other than rectangular, such as a circle.
[0135] An example of how to make a packaging bag using the laminate of the present disclosure will be described. Two laminates are prepared. The two laminates are stacked with their main bodies facing each other. Next, heat seal parts are formed on the three sides of the outer peripheral edge of the laminate, that is, the left and right sides and the bottom. In this way, a packaging bag having an opening on one side is obtained.
[0136] Instead of using two sheets of the laminate of the present disclosure, one sheet of the laminate of the present disclosure may be prepared, folded and stacked so that the second surfaces of the main body of the laminate face each other, and then heat-sealed portions are formed on both the left and right outer peripheral edges to produce a packaging bag. In this way, a packaging bag having an opening on one side is obtained. In this case, a heat-sealed portion may also be formed on the folded lower portion, and further, a lower portion of the lower heat-sealed portion may be cut and removed. This allows the peeling portions to be peeled off on both the front sheet and back sheet of the packaging bag.
[0137] An article is inserted through the opening of the unheat-sealed portion of the packaging bag produced above. The opening of the packaging bag is then heat-sealed to form a heat-sealed portion, thereby obtaining a package in which the article is housed in the packaging bag.
[0138] Fig. 3a is a cross-sectional view showing one embodiment of the packaging bag of the present disclosure. The sealed portion of the packaging bag 50 is formed by overlapping and heat-sealing a laminate 1 having a peel-off portion 2 and a main body portion 4. Fig. 3b is a cross-sectional view showing one embodiment of a usage form of the packaging bag of the present disclosure. For example, the peel-off portions 2, 2 are peeled off from the main body portions 4, 4 of the packaging bag 50, respectively, immediately before being brought into a clean room.
[0139] The packaging bag may have an easy-open portion. Examples of the easy-open portion include a notch portion that serves as a starting point for tearing the packaging bag, and an easy-open line formed by laser processing or a cutter as a path for tearing the packaging bag.
[0140] FIG. 4 is a front view showing one embodiment of the packaging bag of the present disclosure. Hereinafter, an example of the packaging bag will be described with reference to FIG. 4. The packaging bag 50 in FIG. 4 has a storage section 50a for storing an item. The packaging bag 50 includes an upper section 51, a lower section 52, and side sections 53, 53, and has a substantially rectangular outline in a front view. The names "upper section", "lower section", "side section", and terms such as "upper" and "lower" merely relatively indicate the positions and directions of the packaging bag 50 and its components. The posture of the packaging bag 50 during transportation or use is not limited by the names and terms in this specification.
[0141] As shown in Fig. 4, the packaging bag 50 includes a top sheet 54 constituting the top surface and a back sheet 55 constituting the back surface. In the packaging bag 50 shown in Fig. 4, the top sheet 54 and the back sheet 55 are each formed of a single laminate. Although not shown, in the packaging bag 50, the top sheet 54 and the back sheet 55 may be integrated or may be formed of a single laminate. In this case, the laminate is folded back at the lower part 52 so that the main body part constitutes the inner surface of the packaging bag 50. In this case, the packaging bag 50 has a seal part extending along three sides of the packaging bag 50.
[0142] The inner surfaces of the top sheet 54 and the back sheet 55 are joined together by a sealed portion. In the front view of the packaging bag 50 shown in Fig. 4, the sealed portion is hatched. The sealed portion is a portion where the heat-fusible resin layers of the laminate are joined together.
[0143] As shown in Fig. 4, the packaging bag 50 has heat-sealed portions extending along the four sides of the packaging bag 50. The sealed portions include an upper sealed portion 51a extending along the upper portion 51, a pair of side sealed portions 53a, 53a extending along a pair of side portions 53, 53, and a lower sealed portion 52a extending along the lower portion 52. In the packaging bag 50 before an article is contained therein (a state in which no article is contained therein), an opening (not shown) is formed in the upper portion 51 of the packaging bag 50. After an article is contained in the packaging bag 50, the inner surface of the top sheet 54 and the inner surface of the back sheet 55 are joined at the upper portion 51 to form the upper sealed portion 51a and seal the packaging bag 50.
[0144] The upper seal portion 51a, the side seal portions 53a, 53a and the lower seal portion 52a are seal portions formed by joining the inner surface of the top sheet 54 and the inner surface of the back sheet 55 together.
[0145] There is no particular limitation on the method for forming the sealed portion as long as it is possible to join opposing sheets 54, 55 together to seal packaging bag 50. For example, the sealed portion is formed by melting the inner surfaces of the sheets by heating or the like and fusing the inner surfaces together, that is, by heat sealing.
[0146] In one embodiment, the laminate constituting the packaging bag has a half-cut line. The half-cut line is a cut line that extends from the surface of the peel-off portion constituting the laminate to the interface between the peel-off portion and the main body portion, but does not penetrate the laminate. Starting from the half-cut line, the peel-off portion of the laminate can be easily peeled off and removed by hand.
[0147] The position where the half-cut line is formed is not particularly limited. For example, in the case of a packaging bag having a rectangular planar shape, it is preferable to provide the half-cut line at at least one corner of the packaging bag. It is preferable that the half-cut line is formed on both the top sheet and the back sheet of the packaging bag. In one embodiment, the half-cut line extends from the side outer edge to the lower outer edge of the top sheet and the back sheet at the corners of the sheets.
[0148] The half-cut line can be formed, for example, by mechanically cutting the laminate in the thickness direction using a cutter or by irradiating the laminate with a laser. As shown in Fig. 4, a half-cut line 60 is formed at one corner of the sealed portion of the packaging bag 50.
[0149] [Aspects of the present disclosure] The present disclosure relates to, for example, the following [1] to
[13] . [1] A laminate comprising at least a peel-off portion and a main body portion, the peel-off portion being provided so as to be peelable from the main body portion, the peel-off portion containing polyolefin as a main component, the content of the polyolefin in the peel-off portion being 80 mass% or more based on the mass of the peel-off portion, the main body portion containing polyolefin as a main component, the content of the polyolefin in the main body portion being 80 mass% or more based on the mass of the main body portion, the main body portion comprising at least a heat-fusible resin layer containing polyolefin as a main component, and at least one of the peel-off portion and the main body portion comprising a barrier substrate, the barrier substrate comprising a polyolefin substrate containing polyolefin as a main component and a vapor-deposited film provided on the polyolefin substrate. [2] The laminate according to [1], wherein the main body portion comprises the barrier substrate. [3] The laminate according to [1] or [2], comprising the polyolefin substrate in the barrier substrate, the vapor deposition film, and the heat-sealable resin layer, in this order. [4] The laminate according to any one of the above [1] to [3], wherein the barrier substrate comprises an oriented polypropylene substrate containing polypropylene as a main component, and a vapor-deposited film provided on the oriented polypropylene substrate. [5] The laminate according to any one of [1] to [4], wherein the main body portion includes an adhesive layer formed from an adhesive between the barrier substrate and the heat-sealable resin layer. [6] The laminate according to [5], wherein the adhesive layer is an adhesive layer formed from a solvent-free adhesive. [7] The laminate according to [5] or [6], wherein the thickness of the adhesive layer is 0.1 μm or more and 3 μm or less. [8] The laminate according to any one of [1] to [7], wherein the peel-off portion comprises a surface resin layer containing polyolefin as a main component, and an extruded resin layer containing polyolefin as a main component, the extruded resin layer being in contact with a polyolefin substrate constituting the barrier substrate in the main body portion, and the polyolefin in the extruded resin layer is of a different type from the polyolefin in the polyolefin substrate constituting the barrier substrate. [9] The laminate described in [8], wherein the peel-off portion comprises the surface resin layer containing polyethylene as a main component and the extruded resin layer containing polyethylene as a main component, and the main body portion comprises, in this order, the polyolefin base material containing polypropylene as a main component, the vapor-deposited film provided on the polyolefin base material, an adhesive layer formed from an adhesive, and the heat-sealable resin layer containing polyethylene as a main component.
[10] The laminate according to any one of [1] to [9], wherein the content of polyolefin in the laminate is 80 mass % or more based on the mass of the laminate.
[11] The laminate according to any one of [1] to
[10] , wherein the peel strength between the peel portion and the main body portion, measured under conditions of a peel angle of 180 degrees and a test speed of 50 mm / min, is 1.0 N / 15 mm width or less.
[12] A packaging bag comprising the laminate according to any one of [1] to
[11] above.
[13] The packaging bag according to
[12] , having a seal portion formed by joining the heat-sealable resin layers in the laminate. EXAMPLES
[0150] The laminate of the present disclosure will be described more specifically based on examples, but the laminate of the present disclosure is not limited to the examples in any way.
[0151] [Example 1] A film (hereinafter referred to as "transparent vapor-deposited OPP film") was prepared in which a 20 nm thick alumina vapor-deposited film (transparent vapor-deposited film) was provided by PVD on one side of a 18 μm thick biaxially oriented polypropylene film (OPP film) that had been corona-treated on both sides. A 40 μm thick LLDPE film (L-535, additive-free grade, Aicello Co., Ltd.) that had been corona-treated on one side, and a 40 μm thick LLDPE film (NB-1, Tamapoly Co., Ltd.) that had been corona-treated on one side were also prepared.
[0152] The vapor-deposited surface of the transparent vapor-deposited OPP film and the corona-treated surface of the LLDPE film (L-535) were bonded together via a 2 μm-thick adhesive layer made of a solvent-free, two-liquid curing urethane adhesive (RN-800 / HN-800, Rock Paint). The corona-treated surface of the laminated transparent vapor-deposited OPP film and the corona-treated surface of the LLDPE film (NB-1) were bonded together using a melt-extruded LDPE (Novatec LD LC602A, melting point: 107°C, density: 0.919 g / cm 3 The laminate was laminated via a 15 μm-thick extruded resin layer (EC-PE) made of (MFR: 8.2 g / 10 min, Japan Polyethylene Corporation). In this way, a laminate of Example 1 was obtained. The polyolefin content (mass%) of the laminate, the peeled portion and the main body portion was calculated.
[0153] [Example 2] Melt-extruded LDPE (LC602A) was mixed with LLDPE (Harmolex NH845N, melting point: 120°C, density: 0.913g / cm 3 A laminate of Example 2 was obtained in the same manner as in Example 1, except that the polyester resin used was changed to polyethylene terephthalate (MFR: 15 g / 10 min, Japan Polyethylene Corporation).
[0154] [Comparative Example 1] A 12 μm thick transparent vapor-deposited polyethylene terephthalate (PET) film (Techbarrier HX, Mitsubishi Chemical Corporation) was prepared. A laminate of Comparative Example 1 was obtained in the same manner as in Example 2, except that the transparent vapor-deposited OPP film was changed to a transparent vapor-deposited PET film.
[0155] [Making packaging bags] The heat-sealable resin layers of each laminate of the Examples and Comparative Examples were joined together, and the laminates were sealed using a high-speed three-sided automatic bag making machine (BH-60D, manufactured by Totani Giken Kogyo Co., Ltd.) at a temperature of 130°C, a compression time of 1 second, and a pressure of 1 kgf / cm. 2 The mixture was heat sealed under the above conditions to create a three-sided pouch.
[0156] [Physical property evaluation] The methods for evaluating the physical properties of the laminates in the Examples and Comparative Examples are described below. Unless otherwise specified, the environment during measurement of each physical property was a temperature of 23° C. and a humidity of 50% RH. Measurements were performed on three test pieces for each physical property, and the arithmetic mean value of the three values obtained was recorded as the value of each physical property.
[0157] <Peel strength> The laminate was cut to obtain a test piece having a width of 15 mm and a length of 100 mm. Using the test piece and a benchtop tensile compression tester MCT-1150 (manufactured by AND Co., Ltd.) as a measuring instrument, the peel strength (N / 15 mm width) between the peeled part and the main body part in the laminate was measured in accordance with JIS Z1707:2019 under the conditions of an initial chuck distance of 100 mm, a peel angle of 180 degrees, and a test speed of 50 mm / min.
[0158] <Gas barrier property evaluation> The laminate (hereinafter also referred to as the "test piece") was measured for oxygen permeability (cc / (m 2 ·day·atm)) and water vapor permeability (g / (m 2 ·day)) was measured by the following method.
[0159] (Oxygen permeability) The oxygen permeability of the test piece was measured in an environment of temperature 23° C. and humidity 90% RH in accordance with JIS K7126-2:2006 using an oxygen permeability measuring device (OX-TRAN2 / 20 manufactured by MOCON).
[0160] (Water vapor permeability) The water vapor permeability of the test pieces was measured in an environment of temperature 40°C and humidity 90% RH in accordance with JIS K7129-2:2019 using a water vapor permeability measuring device (PERMATRAN-w 3 / 33 manufactured by MOCON).
[0161] <Appearance (floating between layers)> During each process of laminate manufacturing, there was a gap between the peeled part and the main part (air bubbles and white area of 1cm 2 The above-mentioned points were visually inspected. A laminate in which lifting occurred was rated as ×, and a laminate in which lifting did not occur was rated as ◯.
[0162] <Puncture strength> The puncture strength of the laminate was measured in accordance with JIS Z1707:2019. The laminate was cut to obtain a test piece having a width of 5 cm and a length of 5 cm. A tabletop tensile compression tester MCT-1150 (manufactured by AND Co., Ltd.) was used as a measuring instrument. A semicircular needle having a diameter of 1.0 mm and a tip shape radius of 0.5 mm was pierced into the test piece at a test speed of 50 mm / min, and the maximum strength (N) until the needle penetrated the test piece was measured. The above needle was pierced into the heat-sealable resin layer surface (from the inner layer) and the surface resin layer surface (from the outer layer) of the laminate, and the puncture strength (N) of each was measured.
[0163] <Seal strength> The laminate was cut to obtain a test piece having a width of 15 mm and a length of 100 mm. The two test pieces were overlapped so that the heat-sealable resin layers were in contact with each other, and the temperature was 130°C (one-sided heating), the compression time was 1 second, and the pressure was 1 kgf / cm. 2A 15 mm x 15 mm portion of one end of the test piece was heat-sealed under the above conditions to form a sealed portion, and a test specimen was obtained. Except for the following test conditions, the seal strength (N / 15 mm width) was measured in accordance with JIS Z1707:2019 using a tabletop tensile compression tester MCT-1150 (manufactured by AND Co., Ltd.) under the conditions of chuck distance: 100 mm, test speed: 300 mm / min. Specifically, the test specimen was opened 180 degrees so that the sealed portion of the test specimen was in the center of the two grips of the test machine, and both ends of the test specimen were attached to the two grips of the test machine, respectively, and pulled at a speed of 300 mm / min until the sealed portion broke, to obtain the maximum strength (N). The maximum strength (N) measured for the 15 mm wide test specimen was taken as the seal strength (N / 15 mm width).
[0164] <Method for measuring the number of particles in liquid> The number of foreign objects (number of particles) adhering to the surface of the sample bags prepared using each laminate of the Examples and Comparative Examples was measured using a particle counter (KE-40 / KS-40AF, manufactured by Rion Co., Ltd.) under the condition of a measurement size of 0.2 μm or more. The preparation of the sample bags and blank bags was carried out in a clean class 1000 environment. The measurements were carried out in a clean class 100 environment.
[0165] (Method for measuring the number of particles in liquid: Surface of the main body after peeling off the peeled part of the bag) 1. After purging the inside of the measuring device with pure water (25 mL x 4 times), The number of particles in the pure water blank was measured. 2. Blank bags measuring 30cm x 30cm were made using blank film. 3. Using each laminate of the Examples and Comparative Examples, a bag measuring 20 cm x 20 cm was produced. After the opening of the bag was heat sealed, the peelable portion of the bag was peeled off to obtain a sample bag with the surface (peeled surface) of the main body exposed. Two types of test bags were prepared: test bag 1, which had a sample bag placed inside a blank bag, and test bag 2, which was only a blank bag. 4. Pure water whose blank value had been confirmed was poured into the blank bag (outside the sample bag) of test bag 1, and after the pure water had spread over the inner surface of the blank bag and the surface of the sample bag, test bag 1 was left standing for 12 hours or more. In the same way, pure water whose blank value had been confirmed was poured into the blank bag of test bag 2, and after the pure water had spread over the inner surface of the blank bag, test bag 2 was left standing for 12 hours or more. 5. After purging the measuring device with pure water (25 mL x 4 times), the number of particles in the liquid was measured for 10 mL of water collected from test bag 1 and test bag 2 after step "4." above. The blank value for pure water and the number of particles in test bag 2 were subtracted from the number of particles in test bag 1 to calculate the number of foreign objects (number of particles) attached to the surface of the sample bag (surface of the main body of the bag (peeling surface)).
[0166] [Table 1] [Explanation of symbols]
[0167] 1 ...Laminate 2 … Peeling part 4. Main body 10...Barrier substrate 12...Polyolefin base material 14...Vapor deposition film 20…Thermofusible resin layer 30…Surface resin layer 36A…Extruded resin layer 36B…Adhesive layer 40...Goods 50...Packaging bag 50a…Storage section 51…Upper 51a…Upper seal part 52…Lower 52a…Lower seal part 53…Side 53a...Side seal part 54…Surface sheet 55…Back sheet 60...Half cut wire
Claims
1. A laminate including at least a peeling portion and a main body portion, The peeling portion is provided so as to be peelable from the main body portion, the release portion contains polyolefin as a main component, and the content of the polyolefin in the release portion is 80 mass% or more based on the mass of the release portion; The main body contains polyolefin as a main component, and the content of the polyolefin in the main body is 80 mass% or more based on the mass of the main body, and the main body includes at least a heat-sealable resin layer containing polyolefin as a main component; At least one of the release portion and the main body portion comprises a barrier substrate, the barrier substrate comprising a polyolefin substrate containing a polyolefin as a main component and a vapor-deposited film provided on the polyolefin substrate. Laminate.
2. The laminate according to claim 1 , wherein the main body portion comprises the barrier substrate.
3. The laminate according to claim 2 , comprising the polyolefin substrate in the barrier substrate, the vapor-deposited film, and the heat-sealable resin layer, in this order.
4. The laminate according to claim 2 , wherein the barrier substrate comprises an oriented polypropylene substrate containing polypropylene as a main component, and a vapor-deposited film provided on the oriented polypropylene substrate.
5. The laminate according to claim 2 , wherein the main body portion includes an adhesive layer formed from an adhesive between the barrier substrate and the thermally adhesive resin layer.
6. The laminate according to claim 5 , wherein the adhesive layer is an adhesive layer formed from a solvent-free adhesive.
7. The laminate according to claim 5 , wherein the adhesive layer has a thickness of 0.1 μm or more and 3 μm or less.
8. The peeling portion comprises a surface resin layer containing polyolefin as a main component and an extruded resin layer containing polyolefin as a main component, the extruded resin layer is in contact with a polyolefin base material constituting the barrier substrate in the main body portion, and the polyolefin in the extruded resin layer is of a different type from the polyolefin in the polyolefin base material constituting the barrier substrate; The laminate according to claim 2.
9. The peeling portion is The surface resin layer contains polyethylene as a main component; The extruded resin layer contains polyethylene as a main component; Equipped with The main body portion is The polyolefin substrate containing polypropylene as a main component; The vapor-deposited film provided on the polyolefin substrate; an adhesive layer formed from an adhesive; The heat-sealable resin layer contains polyethylene as a main component; The laminate of claim 8 comprising, in that order:
10. The laminate according to claim 1 , wherein the content of the polyolefin in the laminate is 80 mass % or more based on the mass of the laminate.
11. 2. The laminate according to claim 1, wherein a peel strength between the peel portion and the main body portion measured under conditions of a peel angle of 180 degrees and a test speed of 50 mm / min is 1.0 N / 15 mm width or less.
12. A packaging bag comprising the laminate according to any one of claims 1 to 11.
13. The packaging bag according to claim 12 , further comprising a seal portion formed by bonding the heat-fusible resin layers in the laminate to each other.
Citation Information
Patent Citations
Double bag
JP2012126437A